Theoretical models to calculate stopping and ionization ratios of H2+ molecules in solid targets - Archubi, Claudio Darío (2019)
In this work we study the vicinage effects that arise in the interaction of molecular projectiles with solids, considering, in particular, the effects produced by the excitation of inner shells. For this purpose, we use two different approaches. On one side we extend the use of the semiclassical impact-parameter model for the excitation of atomic shells, considering quantum corrections and the role of target screening in the vicinage effects. On the other hand, we adapt our extended wave-packet model, developed in a previous work to the calculation of stopping ratios and ionization cross sections for correlated ions. This model introduces modifications to the wave-packet method originally proposed by Kaneko, using the Levine and Louie technique to take into account the energy gaps corresponding to the different atomic levels of the target. Finally, we add the contribution of valence electrons calculated with the Lindhard free-electron-gas model and compare with experimental results of vicinage effects in the energy-loss and ionization cross sections for hydrogen molecules interacting with C, Al, Si, Al2O3, and SiO2 targets.